Critical Application to the Concept of Formal and Authority Becoming a New Concept of Talent Management - Montoya Monsalve, Juan Nicolas (HUMAN REVIEW. International Humanities Review / Revista Internacional de Humanidades, 2019)
The aim of this paper is to analyze the concept of formal authority in organizations, using a theoretical discussion of its components, their mainstreaming in the administrative process, and its effect on the proactive development of business objects, pretending to determine if this variable is proactive or not, in the development of high performance practices in Human Resource Management, and whether or not a restriction, for people to become their strategic base and/or competitive. We also try, from a case study to determine the effect of expression authority in non-hierarchical designs, the effects of structural position in organizations, the impact of leadership, the relationship of structures and the charges regarding the successes and achievements of the organization, the effect on intra-relationships and communication, imposing, authoritarian, non-cooperation with the lack of consistency with individual purposes, mission and Provisional Record, the continium of bad decisions, relationship with management and control, and finally connect all these elements with the current organizational individuals, immersed in a knowledge society.